2022
DOI: 10.1093/cercor/bhac077
|View full text |Cite
|
Sign up to set email alerts
|

Examining the neural correlates of error awareness in a large fMRI study

Abstract: Goal-directed behavior is dependent upon the ability to detect errors and implement appropriate posterror adjustments. Accordingly, several studies have explored the neural activity underlying error-monitoring processes, identifying the insula cortex as crucial for error awareness and reporting mixed findings with respect to the anterior cingulate cortex (ACC). Variable patterns of activation have previously been attributed to insufficient statistical power. We therefore sought to clarify the neural correlates… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 67 publications
0
11
0
1
Order By: Relevance
“…Finally, we see that the error positivity, Pe, indexing error awareness, is reduced for Distress compared to HC. Less studied than the ERN, the anatomical and functional correlates of the Pe are still being investigated, with some evidence indicating that Pe is a part of the P300 complex (Dali et al., 2023; Ridderinkhof et al., 2009). Although we are not aware of consistent results, evidence suggests an association between reduced Pe and symptoms of depression (Schroder et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we see that the error positivity, Pe, indexing error awareness, is reduced for Distress compared to HC. Less studied than the ERN, the anatomical and functional correlates of the Pe are still being investigated, with some evidence indicating that Pe is a part of the P300 complex (Dali et al., 2023; Ridderinkhof et al., 2009). Although we are not aware of consistent results, evidence suggests an association between reduced Pe and symptoms of depression (Schroder et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Replicating results of Fortenbaugh et al (2018), successful withholding of responses (CO -CE) was associated with greater activity in subcortical, cerebellar, visual, and inferior parietal areas and lesser activity in the medial prefrontal cortex, dorsal anterior cingulate cortex, and insula activity in dataset 2 (but not dataset 1; Figure 1). To our knowledge, few studies have contrasted successful and unsuccessful inhibition directly, but one study which examined these conditions separately found increased cuneus, caudate and inferior frontal activity for successful stopping, and increasing anterior cingulate and insula activity with unsuccessful stopping (Chevrier, Noseworth & Schachar, 2007), both of which have previously been associated with error monitoring and adjustments of control (Ramautar, et al, 2006, Shenhav, Cohen, & Botvinick, 2016, Dali et al, 2023. Our CO -CE contrast then likely captures regions contributing to appropriate motor execution or withholding (subcortical, cerebellar, and inferior parietal areas) during successful inhibition, and error processing and control adjustments (medial PFC, dACC, insula) following unsuccessful inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Successful inhibition was associated with more activity in subcortical and cerebellar regions and visual and inferior parietal areas presumably driven by greater attention-to-task. Unsuccessful inhibition, on the other hand, was associated with greater medial prefrontal and dorsal anterior cingulate cortex and insula activity, potentially reflecting error processing (Dali et al, 2023). A sparser CO-CE map in dataset 1 suggests that this smaller sample may be underpowered to detect effects consistent in Fortenbaugh et al (2018) and dataset 2, although this interpretation of the null effect is speculative.…”
Section: Figure 1 Roi-based Activation Contrasts For Trial-type Event...mentioning
confidence: 95%
“…The anterior cingulate cortex (ACC) is crucial to cognitive control processes as it detects conflicts, initiates the upregulation of cognitive control, and thereby enables improved task performance (21). Besides, the ACC is of importance regarding self-monitoring abilities (48) and strongly associated with error awareness, which is essential to adapt behavior after an error (50). Deficits in ACC function relate to symptoms of ASD such as difficulties in the regulation of attention and rigidity in behavior as well as social-emotional and social-cognitive deficits (32,45,48,49).…”
Section: Introductionmentioning
confidence: 99%
“…Deficits in ACC function relate to symptoms of ASD such as difficulties in the regulation of attention and rigidity in behavior as well as social-emotional and social-cognitive deficits (32,45,48,49). Alongside the ACC, the anterior insula (AI) is relevant to cognitive control processes because its activity reflects a reaction to salient events (e.g., errors) and allows for the subsequent initiation of appropriate control signals (50)(51)(52). In individuals with ASD, abnormalities in AI structure and function have been reported (53-55).…”
Section: Introductionmentioning
confidence: 99%